2022
DOI: 10.21203/rs.3.rs-1176592/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of Action of Zishen Yutai pills in Treating Premature Ovarian Failure Determined by Integrating UHPLC-Q-TOF-MS and Network Pharmacology Analysis

Abstract: Background: Zishen Yutai (ZSYT) pill, a patent Chinese medicine, has been widely used in the treatment of infertility, abortion, and adjunctive treatment of in vitro fertilization (IVF) for decades. Recently, the results of clinical observations showed that premature ovarian failure (POF) patients exhibited improved expression of steroids and clinical symptoms associated with hormone disorders after treatment with ZSYT pills. However, the pharmacological mechanism of action of these pills remains unclear.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Multiple studies have revealed that the proportion of CD4 + T lymphocytes (CD4 + cells), a pro-inflammary T lymphocytes, were elevated in the peripheral blood of POI patients, [72][73][74][75] implying that the enhanced inflammation status might be the risk factors POI. In theory, the potential autoreactive ability of CD4 + cells could be suppressed by regulatory T (Treg) cells, a subset of anti-inflammation T lymphocytes, to maintain the balance between pro-inflammation and anti-inflammation for a healthy immune system.…”
Section: 21 Immune Cell Profiles Of Poi Patientsmentioning
confidence: 99%
“…Multiple studies have revealed that the proportion of CD4 + T lymphocytes (CD4 + cells), a pro-inflammary T lymphocytes, were elevated in the peripheral blood of POI patients, [72][73][74][75] implying that the enhanced inflammation status might be the risk factors POI. In theory, the potential autoreactive ability of CD4 + cells could be suppressed by regulatory T (Treg) cells, a subset of anti-inflammation T lymphocytes, to maintain the balance between pro-inflammation and anti-inflammation for a healthy immune system.…”
Section: 21 Immune Cell Profiles Of Poi Patientsmentioning
confidence: 99%